Analisis Penerapan Kaidah Ejaan Bahasa Indonesia Dalam Artikel Ilmiah Mahasiswa Magister Pendidikan Dasar Universitas Muria Kudus - Ahmad Syukur; Agus Darmuki; Irfai Fathurohman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify errors in the use of Indonesian spelling in scientific journal articles of students at Master of Primary Education, Muria Kudus University published in the Jurnal Prakarsa Paedagogia. A qualitative approach with a descriptive method was used with a focus on two articles published in 2024 as data sources. Data collection was carried out through literature and documentation reviews using inventory techniques, careful reading, and note-taking. The analysis was carried out using a qualitative descriptive method, referring to the Enhanced Spelling Guidelines (EYD) Edition V of the Indonesian Language. The results of the study recorded 99 spelling errors in Indonesian, including 22 spelling errors, 16 errors in the use of capital letters, 27 errors in the use of punctuation, 7 incorrect loan words, 14 preposition errors, 5 repeated word errors, and 8 conjunction errors.